Changes in head posture after rapid maxillary expansion in patients with nasopharyngeal obstruction - Kjurchieva-Chuchkova, Gabriela; Kanurkova, Lidija; Bajraktarova Miševska, Cvetanka (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2017)
Introduction: Nasopharyngeal obstruction is an important etiologic factor in the development of an extreme vertical growth facialpattern, and insufficient transversal growth of the maxilla. The treatment outcomes associated with rapid maxillary expansion in theliterature are mainly discussed in terms of changes in dentofacial morphology, without special reference to changes in the pharyngealairway, the position of the mandible, hyoid bone and the tongue. Aim: The aim of this study was to evaluate the effects of rapid maxillary expansion (RME), on changes in head posture and airway dimension. Materials and methods: The cephalometric evaluation was conducted on thirty lateral cephalograms of patients with nasopharyngeal obstruction (mean age 9.11 years; standard deviation (SD) ± 2.0; range 8-14 years) treated with appliance for rapid maxillary expansion. Patients were randomly divided into two groups: 1) study group comprised of 15 patients treated with RME immediately after the first visit; 2) a control group comprised of 15 subjects monitored for approximately 12 months prior to commencing therapy, who became untreated controls. Lateral cephalograms, taken in the natural head position, were obtained at the first visitand 6 months later for all subjects. Six angular measurements were measured to describe craniocervical angulation, and five linear measurements were measured to describe airway dimension. Results: The investigated group treated with RME shows a statistically significant decrease in craniocervical angulation, especially at the angleof interaction between palatal plane and the tangent odontoid processus (4.07 degrees, for PP/OPT angle) and angle interaction between palatal plane and the tangent of cervical vertebra (4.95 degrees for PP/CVT angle). Airway dimension in the treated group increased, especially at the levels PNS-ad1 (2.52 mm), ve-pve (2.97 mm), and uv-puv (2.88 mm). No significant changes were observed in the control group. Conclusions: RME is a treatment procedure capable of providing increased nasopharyngeal airway adequacy, changing the head posture as well as position of the mandible and tongue, creating the conditions for myofunctional balance and proper development of craniofacial complex and changing mode of respiration.